2023
DOI: 10.1108/lhtn-01-2023-0009
|View full text |Cite
|
Sign up to set email alerts
|

Chatting about ChatGPT: how may AI and GPT impact academia and libraries?

Abstract: Purpose This paper aims to provide an overview of key definitions related to ChatGPT, a public tool developed by OpenAI, and its underlying technology, Generative Pretrained Transformer (GPT). Design/methodology/approach This paper includes an interview with ChatGPT on its potential impact on academia and libraries. The interview discusses the benefits of ChatGPT such as improving search and discovery, reference and information services; cataloging and metadata generation; and content creation, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
313
0
31

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 642 publications
(347 citation statements)
references
References 23 publications
3
313
0
31
Order By: Relevance
“…ChatGPT, as an example of other LLMs, can be described as a promising or even a revolutionary tool for scientific research in both academic writing and in the research process itself. Specifically, ChatGPT was listed in several sources as an efficient and promising tool for conducting comprehensive literature reviews and generating computer codes, thereby saving time for the research steps that require more efforts from human intelligence (e.g., the focus on experimental design) [ 14 , 27 , 28 , 41 , 44 , 46 , 47 , 60 , 71 , 72 ]. Additionally, ChatGPT can be helpful in generating queries for comprehensive systematic review with high precision, as shown by Wang et al, despite the authors highlighting the transparency issues and unsuitability for high-recall retrieval [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ChatGPT, as an example of other LLMs, can be described as a promising or even a revolutionary tool for scientific research in both academic writing and in the research process itself. Specifically, ChatGPT was listed in several sources as an efficient and promising tool for conducting comprehensive literature reviews and generating computer codes, thereby saving time for the research steps that require more efforts from human intelligence (e.g., the focus on experimental design) [ 14 , 27 , 28 , 41 , 44 , 46 , 47 , 60 , 71 , 72 ]. Additionally, ChatGPT can be helpful in generating queries for comprehensive systematic review with high precision, as shown by Wang et al, despite the authors highlighting the transparency issues and unsuitability for high-recall retrieval [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, superficial, inaccurate, or incorrect content was frequently cited as a shortcoming of ChatGPT use in scientific writing [ 14 , 28 , 29 , 40 , 60 ]. The ethical issues including the risk of bias based on training datasets and plagiarism were also frequently mentioned, aside from the lack of transparency regarding content generation, which justifies the description of ChatGPT, on occasions, as a black box technology [ 14 , 25 , 26 , 40 , 44 , 45 , 46 , 47 , 48 , 55 , 60 , 63 , 65 , 72 ]. Importantly, the concept of ChatGPT hallucination could be risky if the generated content is not thoroughly evaluated by researchers and health providers with proper expertise [ 37 , 56 , 73 , 77 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…ChatGPT can support the dissemination and diffusion of new research ideas through the creation of better metadata, indexing, and summaries of research findings (Lund & Wang, 2023). Assuming there is trust and usability among the public, this may support the diffusion of research findings through the translation of research into lay language that can be understood by members of the general public (Wang et al, 2022).…”
Section: Benefits Of Chatgpt For Scholarly Publishingmentioning
confidence: 99%
“…The following common themes emerged from the available literature: ChatGPT as an example of other LLMs can be a promising or even a revolutionary tool for scientific research both in academic writing and in the research process itself. Specifically, ChatGPT was listed in several sources as an efficient and promising tool for conducting comprehensive literature reviews and generating computer codes, thereby saving time for the research steps that require more efforts from human intelligence (e.g., the focus on experimental design) [14,27,32,33,38,47,55,58,78,79]. Additionally, ChatGPT can be helpful in generating queries for comprehensive systematic review with high precision as shown by Wang et al despite the authors highlighting the transparency issues and unsuitability for high-recall retrieval [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of ChatGPT in academic writing and scientific research should be done in light of the following current limitations that could compromise the quality of research: First, superficial, inaccurate or incorrect content was frequently cited as a shortcoming of ChatGPT use [14,47,49,77,79]. The ethical issues including the risk of bias based on training datasets, and plagiarism were frequently mentioned, besides the lack of transparency described on occasions as a black box technology [14,27,[29][30][31][32][33]35,36,39,57,58,77,79]. Importantly, the concept of ChatGPT hallucination was mentioned which can be risky if not evaluated properly by researchers and health providers with proper expertise [59,60,65,73,74].…”
Section: Discussionmentioning
confidence: 99%